2010
DOI: 10.1002/humu.21134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aDMBT1polymorphism associated with increased breast cancer risk and decreased promoter activity

Abstract: According to present estimations, the unfavorable combination of alleles with low penetrance but high prevalence in the population might account for the major part of hereditary breast cancer risk. Deleted in Malignant Brain Tumors 1 (DMBT1) has been proposed as a tumor suppressor for breast cancer and other cancer types. Genomewide mapping in mice further identified Dmbt1 as a potential modulator of breast cancer risk. Here, we report the association of two frequent and linked single-nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…Studies with mice have suggested that DMBT1/ gp340/SAG expression is related to breast cancer susceptibility, being significantly reduced in tumor compared with normal breast tissue (Blackburn et al, 2007). These results have been further confirmed by the identification of two polymorphisms associated with increased risk of breast cancer in women older than 60 years old (Tchatchou et al, 2010). It is noteworthy that one of the polymorphisms was located at the promoter region of the DMBT1 gene and was associated with a significantly reduced promoter activity in vitro.…”
Section: B Therapeutic and Diagnostic Potentialmentioning
confidence: 85%
“…Studies with mice have suggested that DMBT1/ gp340/SAG expression is related to breast cancer susceptibility, being significantly reduced in tumor compared with normal breast tissue (Blackburn et al, 2007). These results have been further confirmed by the identification of two polymorphisms associated with increased risk of breast cancer in women older than 60 years old (Tchatchou et al, 2010). It is noteworthy that one of the polymorphisms was located at the promoter region of the DMBT1 gene and was associated with a significantly reduced promoter activity in vitro.…”
Section: B Therapeutic and Diagnostic Potentialmentioning
confidence: 85%
“…We noted a significant downregulation of Dmbt1 , a glycoprotein of the scavenger receptor cysteine-rich (SRCR) family, with roles in immunity and cancer (Mollenhauer et al 1997). Dmbt1 was identified as a modifier of susceptibility to mammary tumors in Trp53+/− BALB/c breast cancer model (Blackburn et al 2007), and Dmbt1 polymorphisms are associated with increased risk of breast cancer (Tchatchou et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…(13,26) To this end, DMBT1 was proposed as putative tumour suppressor gene for a variety of cancers like brain, (9,27) gastrointestinal, (12,28) breast (10,11,29,30) and lung cancer (31) ; albeit its role might be complex. Other studies showed that DMBT1 is also involved in the development of epithelia and in functions of the immune system.…”
Section: Discussionmentioning
confidence: 99%